Effect of Non-Genetic Factors on Semen Quality of Cocks and Repeatability of Estimates - Sorhue, Ufuoma Godstime; Udeh, Ifeanyichukwu; Edegbo, Joy Afokoghene; Moemeka, Adimabua Mike (Jurnal Sain Peternakan Indonesia, 2024)
Semen quality determines the fertilizing ability of cocks and other male animal’s semen. The goal of this study was to ascertain how ecotype, collection week, cock, and their interactions affected semen quality. The study also estimated the repeatability of some semen quality traits. A total of forty (40) cocks made up of 20 heavy ecotypes and 20 light ecotypes were used for the study. The cocks were individually identified with wing tags. Semen was collected from each cock from 7 am to 10 am every Saturday consistently for six weeks using the abdominal massage technique (AMT). Collected semen was evaluated in terms of volume, concentration, mass density, live sperm, and pH. The results indicated that the week of semen collection significantly affected sperm motility, percent live sperm, and semen pH, while ecotype significantly affected live sperm only. Ecotype x week x cock, interactions significantly affected sperm concentration only. The repeatability of semen quality traits was generally low and ranged from 0.01 ± 0.04 to 0.12 ± 0.04, thus depicting the massive influence of environmental factors on semen quality traits. It is concluded that more than six records are required to characterize the semen-producing ability of the Nigerian indigenous cocks.